IMPLEMENTASI PROGRAM INTERVENSI GIZI SPESIFIK PADA REMAJA PUTRI DAN BALITA DI PUSKESMAS PATEAN KABUPATEN KENDAL - Puriana, Pila; Wigati, Putri Asmita; Nandini, Nurhasmadiar (Jurnal Kesehatan Masyarakat, 2023)
The scope of implementing specific nutrition intervention programs at the Patean Health Center for young women and toddlers in 2021 and 2022 was still not in line with the national target. This study aimed to analyze the implementation of a specific nutrition intervention program for girls and toddlers at the Patean Health Center. This research was a qualitative research with a descriptive approach through in-depth interviews conducted from January to July 2023. The data processing method used content analysis.The results showed that the implementation of the specific nutrition intervention program for young women and toddlers are not optimal. Obstacles in the activities of young women are caused by unclear communication, limited and inadequate support facilities and fragmentation that is not in accordance with policy. Obstacles in toddler activities are caused by limited quality of posyandu cadres, limited budget and inadequate supporting facilities. It can be concluded that the implementation of specific nutrition intervention programs for girls and toddlers at the Patean Public Health Center is not optimal because it is influenced by communication factors, resources, attitudes and bureaucratic structures